The Construction of Simulation Algorithms for Laser Fusion (Communications in Computational Physics, 2018)
In this work, we will present a system of numerical simulations for inertial confinement fusion, which consists of a series of one-dimensional, two-dimensional and three-dimensional codes. Our efforts have been made to develop 2D and 3D computer simulation codes, forming a 2D simulation capability so with the key physics issues in laser fusion can be separately simulated mainly by a LARED family containing six different 2D (and partially 3D) code series. The models and the characteristics of the main codes will be described, and some simulation results using the LARED family will be presented.
Keywords: Laser fusion; numerical simulations; LARED.